Explanation of Agricultural Terms in Dictionaries - Sumaira Nawaz,; Khaitova Gulshan Bahodirovna; Akhmedova Mehrinigor Bahodirovna (Universitas Muhammadiyah Sidoarjo, 2022)
The article is devoted to the agrarian terminology of the German and Uzbek languages, their formation, linguistic analysis, linguistic and cultural features and their place in the terminological system.